A Seal of Prince Domald of Split and Šibenik (Archaeologia Adriatica, 2008)
At the beginning of the 13th century Prince Domald was the most powerful lord in the south of Croatia. No data is recorded about his origins in the historical sources, but he was most probably from the district of Sidraga, between Sukošan and the mouth of the Krka River. He was lord of Zadar in 1204, and lord of Šibenik from 1216 to 1220. King Andrew II granted him Cetina and Trilj in 1210, and he held the fortress of Klis from 1225 to 1227, making problems for the not far distant Trogir. The cities and fortresses under the control of Domald included Split. He became lord of Split from before the 25th of March 1207, and he remained in this position to the end of 1220, or the beginning of 1221, when he was replaced by Višen from the Luka district, in the hinterland of Zadar. He again became lord of Split in 1234 or the beginning of 1235, but only to 1237, when he was replaced by Prince Marko, the son of Grgur of Bribir.In the manuscript book of heraldic devices of Dujam Srećko Karaman the seal of Domald is drawn, with an eagle with spread wings and head turned to the right, holding in its talons a snake, surrounded by the legend: SIGILLVM DOMALDI SPALATENSIS ET SIBENICENSIS COMITIS. Such an appearance of this seal was known to Ivan Lučić Lucius, as can be seen from his correspondence with the Zadar archdeacons Valerius Ponte and Fran Divnić (Difnik) from 1667. The seal is important as it shows that Domald was neither from the Kačić nor from the Nelipić clan. The original blazon of the Kačić family was a winged dragon, while the coat-of-arms of the Nelipić family is known from the seal of the lord of Cetina and Klis Ivan (Ivaniš) from 1418, bearing a crown from which rises a stylized lily with one globe on each side.
Keywords: Prince Domald; seals; coats-of-arms; Split; Šibenik